Greater loss of horizontal force after a repeated-sprint test in footballers with a previous hamstring injury - Lord, C.; Blazevich, A. J.; Drinkwater, E. J.; Maayah, F. (Journal of Science and Medicine in Sport, 2019)
Objectives: To quantify changes in running kinetics and kinematics during a repeated-sprint test in football players, and explore the sensitivity and specificity with which these variables can identify previous hamstring injury. Design: 20 Western Australia State League footballers with previous unilateral hamstring injury and 20 players without completed a 10 × 6-s repeated-sprint test on a non-motorised treadmill dynamometer. Methods: Changes in horizontal force, vertical force, contact time and flight time were compared between previously injured and uninjured legs of participants. Results: Mean horizontal force production of the previously injured leg in the injured group was 13% lower (p = 0.001), and this magnitude of change was used to identify the injured legs within the cohort with 77% specificity and 85% sensitivity. Furthermore, the area under the Receiver Operating Characteristics curve (0.846) demonstrated that the between-leg difference in mean horizontal force was a good instrument for identifying previous hamstring injury. Conclusions: There is a greater fatigued-induced change in mean horizontal force during a repeated-sprint test in legs with previous hamstring injury than the non-injured legs of the injured players or the legs of uninjured players. Such asymmetry may contribute to impaired performance in football players returning from hamstring injury and also to the high rate of hamstring re-injury. Rehabilitation and return-to-play strategies should emphasise a reduction in asymmetry, particularly during repeated high-intensity efforts. Furthermore, binary regression and Receiver Operating Characteristic analyses suggest that changes in mean horizontal force could be used to assess risk of hamstring injury, re-injury and/or return to play.